Locating vaccine uptake and public participation in Ukraine: An exploratory qualitative study on attitudes and barriers to early childhood vaccination - Jacob Osborne; Maria Goncharova; Miroslava Germanovich; Oksana Koshalko; Ruth Kutalek; Michel Dückers; Roman Rodyna (Taylor & Francis Group, 2023)
A growing body of literature on vaccine hesitancy considers context and the intersecting factors affecting vaccine uptake. This study attempts to add focus to the conversation of vaccines in Ukraine by exploring how vaccines are perceived and how local stakeholders envision solutions to the problems surrounding vaccine uptake. Twenty-five in-depth interviews were carried out among parents of children under 6 years of age as well as health practitioners and other experts in Ukraine. Results were presented to stakeholders during a dialogue session to discuss the implications for policy recommendations. The Roma parents interviewed faced structural barriers to vaccine access, while other groups received vaccine information from others in their communities, such as family members or religious organisations. Mistrust of the health system and lack of access to reliable information preceded many doubts parents expressed surrounding vaccines. Stakeholders agreed that better, more targeted communication strategies are needed, as well as increased engagement with and training of medical practitioners. Qualitative methods allowed for a deeper, more nuanced understanding of the factors contributing to low vaccine uptake, of which vaccine hesitancy is only one part. The vulnerability-informed approach used may have broader applications for community engagement and responding to infectious diseases and crises.